please do it...................
Attachments:
![](https://hi-static.z-dn.net/files/db9/ae2bdc70ceb909541f0749de10a1736f.jpg)
Answers
Answered by
0
can you write and give this as a question
arshi82:
You know one thing about you that you are blind
Answered by
0
For the first leg of the journey,
V = 0 + α t1
So V = α t1
for the second leg of journey of duration t - t1 :
0 = V - β (t - t1)
0 = α t1 - β t + β t1
t1 = β t / (α + β)
V = αt1 = α β t / (α + β )
Attachments:
![](https://hi-static.z-dn.net/files/d0b/8240d743453ebb6b8fb6770e4c574a69.jpg)
Similar questions